Shares in students: A new model for university funding - Peter Ainsworth (Institute of Economic Affairs (IEA), 2024)
Urgent financial crisis: The government's inflation based increase in 2025 tuition fees from 9,250 to 9,535 will generate only 330 million, less than the 370 million burden created by its budget. With university finances set to continue to deteriorate, and some institutions on the brink of failure, the UK's global standing as a toptier higher education provider is at stake. This crisis necessitates bold, innovative reforms. Outdated centralisation: Centralised state funding and control of universities, a relic of the post-1918 Haldane Report, has eroded financial independence. A century later, the report's wartime-inspired model, built on the flawed belief that government could efficiently direct the economy in peacetime, has plainly failed, with universities facing unsustainable financial pressures. Learning from history: There is much to be learned by looking back before 1918, to the mediaeval period, when the first universities were created. These were the incorporated craft guilds, which trained apprentices in exchange for a share of the apprentice's work product once they became productive. This system of aligned incentives is considered the basis of Europe's successful transmission of technical and business knowledge throughout society, leading to the Industrial Revolution. Revisiting these principles would provide a model for sustainable, incentive-aligned higher education. Flawed incentives in current lending: Where government issues student loans it frees universities from repayment risk which encourages them to focus on recruitment rather than on improving graduate employability. This results in growing enrolments but poor employment outcomes, with one in five graduates earning less than if they had not attended university. Structural reform: Drawing from the master-apprentice model, the paper proposes that universities lend directly to students. This arrangement of income contingent loan (ICL) financing will ensure universities only succeed financially if their students do. Thus, institutions would be incentivised to only recruit students who are ready for serious study and to design courses that lead to workplace success. Fee autonomy with conditions: Universities should be allowed to set their own fees above 9,535, which becomes a cap on the level of the state loan, provided they make available ICLs for any excess, ensuring access for all. This would promote financial sustainability while allowing top institutions to invest in quality, and lowertariff universities to differentiate with cost effective offerings. The government loan cap would remain fixed indefinitely to gradually phase out state dependency. Cutting red tape: With universities motivated by employability outcomes, regulation of course content is redundant and should be abolished. This would reduce the burden of red tape, freeing academics to design courses that will better prepare their students for successful careers. Student protection: To safeguard students, the Office of the Independent Adjudicator should be empowered to award financial compensation for misleading claims about educational outcomes. This would compel universities to make honest statements about employability prospects and the commitment required from students, thus ensuring transparency and accountability. Reconsidering charitable status: The government proposal to tax private schools challenges the notion of education as a universal charitable activity. With many universities receiving the majority of their income as payment for services which benefit, in the main, the more prosperous elements of society, the case for charitable status is weakened. There is thereby an argument for removing charitable status from universities, and instead putting investment in human capital on the same footing as investment in physical capital by, for example, making income contingent repayments tax deductible.
Keywords: 330